The Role of Na+ and K+ Transporters in Salt Stress Adaptation in Glycophytes - Assaha, Dekoum V. M.; Ueda, Akihiro; Saneoka, Hirofumi; Al-Yahyai, Rashid; Yaish, Mahmoud W. (Frontiers in Physiology, 2017)
Ionic stress is one of the most important components of salinity and is brought about by excess Na+ accumulation, especially in the aerial parts of plants. Since Na+ interferes with K+ homeostasis, and especially given its involvement in numerous metabolic processes, maintaining a balanced cytosolic Na+/K+ ratio has become a key salinity tolerance mechanism. Achieving this homeostatic balance requires the activity of Na+ and K+ transporters and/or channels. The mechanism of Na+ and K+ uptake and translocation in glycophytes and halophytes is essentially the same, but glycophytes are more susceptible to ionic stress than halophytes. The transport mechanisms involve Na+ and/or K+ transporters and channels as well as non-selective cation channels. Thus, the question arises of whether the difference in salt tolerance between glycophytes and halophytes could be the result of differences in the proteins or in the expression of genes coding the transporters. The aim of this review is to seek answers to this question by examining the role of major Na+ and K+ transporters and channels in Na+ and K+ uptake, translocation and intracellular homeostasis in glycophytes. It turns out that these transporters and channels are equally important for the adaptation of glycophytes as they are for halophytes, but differential gene expression, structural differences in the proteins (single nucleotide substitutions, impacting affinity) and post-translational modifications (phosphorylation) account for the differences in their activity and hence the differences in tolerance between the two groups. Furthermore, lack of the ability to maintain stable plasma membrane (PM) potentials following Na+-induced depolarization is also crucial for salt stress tolerance. This stable membrane potential is sustained by the activity of Na+/H+ antiporters such as SOS1 at the PM. Moreover, novel regulators of Na+ and K+ transport pathways including the Nax1 and Nax2 loci regulation of SOS1 expression and activity in the stele, and haem oxygenase involvement in stabilizing membrane potential by activating H+-ATPase activity, favourable for K+ uptake through HAK/AKT1, have been shown and are discussed.